Exploring the threshold of human activity impact on urban ecosystem service value: a case study of Hefei, China - Yao, Zhiqiang; Chen, Shi; Huang, Yinlan (Scientific reports, 2025)
Investigating the intricate relationship between human activities and ecosystem service value (ESV) amid rapid urbanization is essential for advancing urban ecological sustainability and development. While previous research has extensively documented the broad impacts of human activities on ESV, several critical gaps remain in our understanding. Specifically, the mechanisms through which human activities affect ecosystem services with varying functions remain unclear. Additionally, the identification of local anomalies in the spatiotemporal association between human activities and ESV is still lacking. These gaps hinder our ability to develop targeted strategies for maintaining ESV equilibrium in the face of ongoing urbanization. To address these gaps, this research employed Land Use and Land Cover (LULC) data from Hefei spanning 2000 to 2020. An equivalent factor corrected ESV assessment model, an ESV flow matrix, a human activity intensity (HAI) measurement model, and a GeoDetector model were utilized to conduct a comprehensive analysis. The objective was to elucidate the driving mechanisms of HAI on ESV, establish clear thresholds for HAI’s impact on various functional components of ESV, and accurately identify localized ranges of anomalous impact. The results indicate that: (1) The ESV of Hefei declined continuously from 47.012 billion yuan in 2000 to 45.534 billion yuan in 2020. (2) This decline was attributed to increased losses and decreased gains. Losses primarily stemmed from the conversion of cropland to built-up land and the transformation of water area into cropland, while gains mainly originated from the reversion of built-up land to cropland and the conversion of cropland to water area. (3) HAI demonstrated a negative correlation with overall ESV, as well as with regulating and cultural service value, and displayed a transition from positive to negative effects on supporting and provisioning service, with the transition threshold range locked between 0.176 and 0.262. HAI exhibited three abnormal impact ranges on ESV, suggesting that strategic land management could sustain ESV equilibrium under both low and high intensities of human activity. This study fills a significant gap in our understanding of the threshold effects of HAI on different functional components of ESV and the identification of local anomalous information. These findings provide a scientific basis for urban ecological environment management and decision-making in the process of rapid urbanization.